2016
DOI: 10.1177/1476718x15616834
|View full text |Cite
|
Sign up to set email alerts
|

Pre-primary education and long-term education performance: Evidence from Programme for International Student Assessment (PISA) Thailand

Abstract: Several research papers have assessed the long-term benefits of pre-primary education in terms of academic performance and labor market outcomes. This study analyzes data obtained from the Programme for International Student Assessment (PISA) to estimate the effects of preschool enrollment of Thai students on producing long-term benefits in their academic performance. Results show that a mother’s educational attainment has a significant impact on the decision to enroll her child in preschool. Regarding the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
(30 reference statements)
2
21
0
5
Order By: Relevance
“…El tratamiento de estos datos permite la generación de investigaciones, como las realizadas por Vidal, Díaz y Jarquín (2004), que establecen relaciones entre el desempeño escolar y determinados factores demográficos. Este tipo de investigaciones son de reconocido interés debido a que brindan información sobre los factores que influyen en el rendimiento escolar del alumnado y permiten a las instituciones educativas gestionar mejor sus recursos al orientarlos a determinados colectivos (Benavides, León y Etesse, 2014) o fomentar innovaciones y mejoras en determinadas etapas educativas (Pholphirul, 2017).…”
Section: Estado De La Cuestiónunclassified
“…El tratamiento de estos datos permite la generación de investigaciones, como las realizadas por Vidal, Díaz y Jarquín (2004), que establecen relaciones entre el desempeño escolar y determinados factores demográficos. Este tipo de investigaciones son de reconocido interés debido a que brindan información sobre los factores que influyen en el rendimiento escolar del alumnado y permiten a las instituciones educativas gestionar mejor sus recursos al orientarlos a determinados colectivos (Benavides, León y Etesse, 2014) o fomentar innovaciones y mejoras en determinadas etapas educativas (Pholphirul, 2017).…”
Section: Estado De La Cuestiónunclassified
“…Unfortunately, some school going children are constrained to join parents to fend for daily bread (Gbollie and Keamu, 2017), contrary to the advice to keep children free from economic activity (Wrigley, 2016), because it is gradually becoming an obstacle to children accessing education (McKinney, 2014). On the other hand, evidence has revealed that socio-economic status of parents and other characteristics plays an important role in promoting quality education and better learning outcomes for students (Fasina, 2011;Center on Education Policy, 2012;Cetin and Taskin, 2016;Pholphirul, 2017).…”
Section: High Poverty Ratementioning
confidence: 99%
“…As a result, many schools operate under difficult circumstances ranging from poor learning facilities to unqualified teachers. To change the trend requires more practical and action-oriented financial and moral support from government to resuscitate the sector (Gbollie and Keamu, 2017;Pholphirul, 2017).…”
Section: Low Budgetary Support For Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding to the advantages of early childhood education, Pholphirul (2017) assessed the access to and the long term benefits of pre-primary education for Thai students by using test scores from PISA. Even though results indicated that early childhood education had a significant effect on scoresin reading, mathematics, and science when the children reached age 15, unequal access to pre-primary education remained a major obstacle for Thai children to reap benefits from attending preschool.…”
Section: Introductionmentioning
confidence: 99%